Particle strengthening of metals and alloys - Nembach, E. (Eckhard)
A thorough understanding of the processes governing particle strengthening of metals and alloys is crucial for anyone engaged in developing structural materials or designing with them. Now you can have easy access to the information you need with this unique guide, the most comprehensive and up-to-date resource available on this important subject.